Looking for trustworthy answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
Sure! Let's expand the expression [tex]\((2x^4 + 5y)^3\)[/tex] step-by-step.
To expand [tex]\((a + b)^3\)[/tex], we can use the binomial theorem, which states:
[tex]\[ (a + b)^3 = a^3 + 3a^2b + 3ab^2 + b^3 \][/tex]
In this case, [tex]\(a = 2x^4\)[/tex] and [tex]\(b = 5y\)[/tex].
Now we will substitute [tex]\(a = 2x^4\)[/tex] and [tex]\(b = 5y\)[/tex] into the binomial expansion formula.
1. Calculate [tex]\(a^3\)[/tex]:
[tex]\[ (2x^4)^3 = 2^3 \cdot (x^4)^3 = 8x^{12} \][/tex]
2. Calculate [tex]\(3a^2b\)[/tex]:
[tex]\[ 3 \cdot (2x^4)^2 \cdot 5y = 3 \cdot (2^2 \cdot (x^4)^2) \cdot 5y = 3 \cdot 4x^8 \cdot 5y = 60x^8y \][/tex]
3. Calculate [tex]\(3ab^2\)[/tex]:
[tex]\[ 3 \cdot (2x^4) \cdot (5y)^2 = 3 \cdot 2x^4 \cdot 25y^2 = 3 \cdot 50x^4y^2 = 150x^4y^2 \][/tex]
4. Calculate [tex]\(b^3\)[/tex]:
[tex]\[ (5y)^3 = 5^3 \cdot y^3 = 125y^3 \][/tex]
Now, combine all these terms:
[tex]\[ 8x^{12} + 60x^8y + 150x^4y^2 + 125y^3 \][/tex]
So, the expanded form of the expression [tex]\(\left(2x^4 + 5y\right)^3\)[/tex] is:
[tex]\[ 8x^{12} + 60x^8y + 150x^4y^2 + 125y^3 \][/tex]
To expand [tex]\((a + b)^3\)[/tex], we can use the binomial theorem, which states:
[tex]\[ (a + b)^3 = a^3 + 3a^2b + 3ab^2 + b^3 \][/tex]
In this case, [tex]\(a = 2x^4\)[/tex] and [tex]\(b = 5y\)[/tex].
Now we will substitute [tex]\(a = 2x^4\)[/tex] and [tex]\(b = 5y\)[/tex] into the binomial expansion formula.
1. Calculate [tex]\(a^3\)[/tex]:
[tex]\[ (2x^4)^3 = 2^3 \cdot (x^4)^3 = 8x^{12} \][/tex]
2. Calculate [tex]\(3a^2b\)[/tex]:
[tex]\[ 3 \cdot (2x^4)^2 \cdot 5y = 3 \cdot (2^2 \cdot (x^4)^2) \cdot 5y = 3 \cdot 4x^8 \cdot 5y = 60x^8y \][/tex]
3. Calculate [tex]\(3ab^2\)[/tex]:
[tex]\[ 3 \cdot (2x^4) \cdot (5y)^2 = 3 \cdot 2x^4 \cdot 25y^2 = 3 \cdot 50x^4y^2 = 150x^4y^2 \][/tex]
4. Calculate [tex]\(b^3\)[/tex]:
[tex]\[ (5y)^3 = 5^3 \cdot y^3 = 125y^3 \][/tex]
Now, combine all these terms:
[tex]\[ 8x^{12} + 60x^8y + 150x^4y^2 + 125y^3 \][/tex]
So, the expanded form of the expression [tex]\(\left(2x^4 + 5y\right)^3\)[/tex] is:
[tex]\[ 8x^{12} + 60x^8y + 150x^4y^2 + 125y^3 \][/tex]
Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.